THE INFLUENCE OF STRATEGIC LEADERSHIP OF ACADEMIC LEADERS ON THE MEDIATION OF PROFESSIONAL TRAINING AND STAFF PERFORMANCE - Chamisah, Chamisah; Othman, Azam bin; Ibrahim, Muhammad Burhan (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2023)
This research aims to examine the influence of strategic leadership of academic leaders (SLAL) as a mediator between professional training (PT) and staff performance (SP) in state Islamic higher education institutions in Aceh. The study selected a sample of 526 individuals from a population of 826 within five state Islamic higher education institutions in Aceh. Descriptive statistics using SPSS version 22.0 were employed, along with Confirmatory Factor Analysis (CFA) and Structural Equation Modeling (SEM) using AMOS software version 23.0 to analyze the data, address research questions, and test hypotheses. The findings from the CFA revealed that professional training (PT) consists of five distinct factors, indicating that all dimensions of professional training (PT) contribute to the latent variable of professional training. Similarly, strategic leadership of academic leaders (SLAL) comprises seven distinct factors, representing the different dimensions of strategic leadership of academic leaders (SLAL) and contributing to the latent variable of strategic leadership. Furthermore, staff performance (SP) consists of four distinct factors, representing the various dimensions of staff performance and contributing to the latent variable of staff performance in state Islamic higher education institutions. Additionally, the study identified a significant relationship between professional training (PT) and staff performance (SP) mediated by strategic leadership of academic leaders (SLAL). This indicates that strategic leadership plays a mediating role in the relationship between professional training and staff performance in state Islamic higher education institutions in Aceh.